Expression of Employer's Demands in Local Legal Regulations - Tatiana M. Ponomareva (Сибирское юридическое обозрение, 2016)
The publication outlines the main scientific views on the issue of local content regulations, the structure of the rules of their filling. The author explores the principles of the internal labor regulations of the organization. The role of incentives, encouraging labour regulations as the specific features of the local employer's rulemaking, expressing its requirements to employees, are analyzed.